Futures of European welfare models and policies – Seeking actual research questions, and new problem-solving arsenal for European welfare states - Erik överland; Jari Kaivo-oja; Erik Terk; Anu Toots; Külliki Tafel-Viia; Andres Viia; Silja Lassur; Bostjan Kerbler; Richard Sendi; Barbara Cernik Mali; Joe Finnery; Mairead Considine (Springer, 2022)
The key research question is to discuss and elaborate the potential value added that futures studies could provide for European citizens and political, social and economic institutions. In the article the problems of European welfare policy issues are theoretically described and analysed. In the article broader framework to understand key policy issues of European welfare policy challenges are defined. A general analysis and generic model for European welfare policy is presented. The Authors also present futures oriented methodological approach to analyse and solve new challenges of European welfare policy problems. Key contributions of this article are: (1) Analysis of theoretical basis for construction of welfare models in future environments, (2) the relationship between research questions and topics in welfare policy planning and management, (3) the analysis of the relationship between futures oriented research questions, methodological stages and outcomes in the field of European welfare policy and (4) the concrete methodological proposal how futures research methodology can help to solve future puzzles of European welfare policy.